RANCANG BANGUN APLIKASI KONVERSI FILE BERFORMAT IMAGE MENJADI FILE BERFORMAT TXT - Napitupulu, Revida Iriana; Mauludin, Muhammad Fikri; Gianadevi, Fettiana; Rumambi , Tavipia (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
So far, the process carried out by users or document owners to convert written documents into digital format must be processed manually, namely by retyping the document. Moreover, the documents to be converted are complex will be very difficult to do. Retyping that is too Long will be prone to typing errors and require more thorough editing. The process can be helped by making an application to convert image format files into text format files equipped with image compression techniques so that when uploading images to the application does not take too long. Making an application extracts files with image extensions into txt extension files using the waterfall method with four stages, namely stage (1). needs analysis, (2). designing, (3) coding, (4) testing. The output of this research is an application to extract image extension files into txt extension files that are expected to meet user needs and expectations and have a good level of accuracy and performance so that it can provide benefits in sorting or converting image extension files into txt extension files.